Opportunities for and constraints to women’s empowerment in Tanzania’s cashew value chain - Aku, Aika; Mpenda, Zena; Mpunde, Venance; Bryan, Elizabeth; Mather, David L. (Michigan State University Press, 2023)
Cashew is a cash crop primarily grown by smallholder farmers in Tanzania and is a major source of rural employment and income in Coastal areas. Women dominate small-scale cashew processing yet face various constraints to increasing their productivity and profitability. This study assesses the effectiveness of an intervention that provided equipment and training to women’s cashew processing groups (WCPGs) in Mtwara and Lindi regions, implemented by the Small Industries Development Organization (SIDO). The study uses mixed methods including in-depth focus group discussions with WCPGs, male and female cashew farmers, and other stakeholders in the cashew value chain, data on WCPG processing productivity, costs, revenues, and profitability with and without the improved processing equipment. The findings indicate that groups using this equipment can process 3 times as much RCN per day compared with the quantity that they could process before using rudimentary shelling tools. This results in participating WCPGs producing about 85 percent more processed cashew per season on average compared with a control group of WCPGs, and 3 times higher profits per season. However, participating WCPGs still face constraints including credit for accessing raw cashew and reliable access to markets for their processed cashew. The results suggest that this and similar interventions need to take a more holistic approach, recognizing that a technology intervention intended to increase production should be complemented by efforts to alleviate input and output marketing constraints.